DMFT study of the local correlation effects in quasi-periodic system. (18th March 2015) - Takemori, Nayuta; Koga, Akihisa
Abstract: We study a two-dimensional Hubbard model on a Penrose lattice by means of the real-space dynamical mean-field theory. Calculating the renormalization factor and density of states at each site, we discuss local electron correlations on the quasi-periodic structure. It is found that the renormalized metallic state appears near the Mott transition in the Penrose lattice system. We also address a spatially-dependent renormalization characteristic of the quasi-periodic lattice.